Characterization and Wear Behaviour of WC-Co Coated Copper under Dry Sliding Conditions at Varying Hardness - R. Jojith; N. Radhika; R. Vigneshwar Raj (Tribology in Industry, 2020)
Pure copper was coated with Tungsten Carbide-Cobalt (WC12%-Co) using Detonation- Gun technique. A coating thickness of 541 µm was obtained and the hardness of WC-Co coated copper surface was 5.2 times greater than the hardness of uncoated surface. The wear properties of coated copper were investigated using pin-on-disc tribometer, where the WC-Co coated copper exhibited higher wear resistance than uncoated copper. Dry sliding wear properties of WC-Co was analysed using Response Surface Methodology by considering the parameters load (10, 20, 30 N), sliding velocity (0.75, 1.5, 2.25 ms-1) and sliding distance (750, 1250, 1750 m). The results indicated an increase in the wear rate with increasing load and velocity, whereas the increase in the distance showed minimal increase in wear rate. The worn surfaces were analysed using Scanning Electron Microscopy to understand the wear mechanism. The result from the presented experiment may find its application in clutch selector fork of automobile transmission and bearings.